High-temperature lasing characteristics of randomly assembled SnO2 backbone nanowires coated with ZnO nanofins - Yang, H. Y. (2014)
Lasing characteristics of randomly assembled SnO2 backbone nanowires coated with ZnO nanofins are investigated. It is shown that the hierarchical nanostructures can sustain ultraviolet random lasing action even at substrate temperature higher than 700 K and the corresponding characteristic temperature is found to be about 390 K. This is because the presence of ZnO nanofins improves heat transfer from the SnO2 backbone nanowires to the surrounding. Hence, some portion of the hierarchical nanostructures can be cooled down and the corresponding optical gain can be maintained even at high substrate temperature.